Energy‐aware scheduling mandatory/optional tasks in multicore real‐time systems. (8th August 2016) - Méndez‐Díaz, Isabel; Orozco, Javier; Santos, Rodrigo; Zabala, Paula
Abstract: Reward‐based scheduling of real‐time systems of periodic, preemptable, and independent tasks with mandatory and optional parts in homogeneous multiprocessors with energy considerations is a problem that has not been analyzed before. The problem is NP‐hard. In this paper, a restricted migration schedule is adopted in which different jobs of the same task may execute in different processors and at different power modes but no migration is allowed after the job has started its execution. An objective function to maximize the performance of the system considering the execution of optional parts, the benefits of slowing down the processor, and a penalty for changing the operation frequency is introduced together with a set of constraints that guarantee the real‐time performance of the system. Different algorithms are proposed to find a feasible schedule maximizing the objective function and are compared using synthetic systems of tasks generated following guidelines proposed in previous papers.